2016
DOI: 10.1039/c6ob00854b
|View full text |Cite
|
Sign up to set email alerts
|

Genetic incorporation of 1,2-aminothiol functionality for site-specific protein modification via thiazolidine formation

Abstract: Here we report a new site-specific conjugation strategy to modify proteins via thiazolidine ligation. Proteins harbouring a 1,2-aminothiol moiety introduced by amber codon suppression technology could be modified chemoselectively with aldehyde-functionalized reagents, such as a biotin-labeled peptide or ubiquitin, under mild conditions to yield homogeneous biotinylated or ubiquitinated products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 37 publications
(12 reference statements)
0
25
0
Order By: Relevance
“…As a result there are a limited number of examples in the literature where such reactions have been performed under neutral conditions and it is generally suggested that thiazolidine formation requires acidic conditions and the products are unstable under neutral conditions. 26,27,[34][35][36][37][38][39][40][41][42] We believe that the different intensities of the two sets of signals observed at pD 7.4 are due to the interaction of the carboxylic acid with the syn-NH protons that form a zwitterion which makes the deprotonation of the anti-NH proton more favorable. The structure of the thiazolidine ring was systematically characterized using 1D and 2D NMR spectroscopic analyses with the purified product 3 (Fig.…”
Section: And Fig S1-s8 Esi †) At Pd = 3 Thiazolidine Formation Wasmentioning
confidence: 96%
See 1 more Smart Citation
“…As a result there are a limited number of examples in the literature where such reactions have been performed under neutral conditions and it is generally suggested that thiazolidine formation requires acidic conditions and the products are unstable under neutral conditions. 26,27,[34][35][36][37][38][39][40][41][42] We believe that the different intensities of the two sets of signals observed at pD 7.4 are due to the interaction of the carboxylic acid with the syn-NH protons that form a zwitterion which makes the deprotonation of the anti-NH proton more favorable. The structure of the thiazolidine ring was systematically characterized using 1D and 2D NMR spectroscopic analyses with the purified product 3 (Fig.…”
Section: And Fig S1-s8 Esi †) At Pd = 3 Thiazolidine Formation Wasmentioning
confidence: 96%
“…32,33 In spite of the large body of literature on the 1,2-aminothiol reaction with aldehydes, there has been limited information on the rate of the reaction and stability of the thiazolidine products under physiological conditions. 26,27,[34][35][36][37] It is generally believed that the reaction requires acidic pH 26,35,[37][38][39][40] and a long reaction time, 26,27,[34][35][36][37][38][39] and that the thiazolidine product is prone to undergo hydrolysis under physiological conditions. 26,27,34,40,41 A lot of research has been dedicated to achieving stable thiazolidine products by designing different substrates.…”
mentioning
confidence: 99%
“…21 Liu's group reported the use of methylester form of L-ThzK to achieve good yield of UB expression in E. coli cells. [22][23] Here we carried out a detailed comparison of the yields of L-and D-ThzK incorporation between the methylester and free acid forms of the UAA and found ThzK methylester could enhance UAA incorporation by ~6 fold. We also found the incorporation of BocK and Prk UAA were benefitted from using their methylester forms.…”
mentioning
confidence: 95%
“…Further work demonstrated the importance of configuration and PylRS variant, as the wildtype M. mazei PylRS could recognise ( S )‐ 64 but not ( R )‐ 64 , thus exhibiting greater sensitivity to the configuration of the Cys chiral centre . Directed evolution of the M. barkeri PylRS led to improved recognition of ( S )‐ 64 and ( R )‐ 64 , as well as compatibility with the reactive amino acid 65 a , a 4‐thiazolidine derivative of ( R )‐ 64 (designed to circumvent pyruvate adduct formation), which, once unmasked with methoxyamine, could undergo bioorthogonal cyanobenzothiazole condensation with fluorophores or aniline‐catalysed thiazolidine formation with aldehyde‐tagged ubiquitin (Scheme ) . The analogous 2‐thiazolidine 65 b , used with wild‐type M. barkeri PylRS as a racemate, was also found to be a useful cage for reactivity.…”
Section: Recognising Phenylalanine and Cysteine Analogues By Using Pymentioning
confidence: 99%
“…[71] Directed evolution of the M. barkeri PylRS led to improved recognition of (S)-64 and (R)-64,a sw ell as compatibility with the reactive amino acid 65 a,a4-thiazolidine derivativeo f( R)-64 (designed to circumvent pyruvate adduct formation), which, once unmasked with methoxyamine, could undergo bioorthogonalc yanobenzothiazole condensation with fluorophores or aniline-catalysed thiazolidine formation with aldehyde-tagged ubiquitin (Scheme 10). [72] The analogous 2-thiazolidine 65 b,u sed with wild-type M. barkeri PylRS Scheme8.Phenylalanine and derivatives compatible with am utated PylRS. ChemBioChem 2017ChemBioChem , 18,1973ChemBioChem -1983 www.chembiochem.org as ar acemate, was also found to be auseful cage for reactivity.…”
Section: Recognising Phenylalanine and Cysteine Analogues By Using Pymentioning
confidence: 99%